Pengaruh Model Pembelajaran POE2WE (Prediction, Observation, Explanation, Elaboration, Write, and Evaluation) terhadap Kemampuan Koneksi Matematis Peserta Didik - Anggraeni, Putri Dwi; Kurniawan, Dian; Mansyur, Muhammad Zulfikar; Yulianto, Eko (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2024)
Abstract: this research is aims to determine the effect of the POE2WE learning model in students’ mathematical connection abilities. The research approach used is a quantitative approach with an experimental method. The research design used is a true experimental design in the form of posttest-only control design with the POE2WE learning model as the independent variable and mathematical connection ability as the dependent variable. The population in this study was all class VIII SMP Al Islam Islamic Boarding School Cirebon, samples were taken from two selected classes, class VIII G as the experimental class and class VIII H as the control class. Data collection was carried out using test techniques. The instrument used is a mathematical connection ability test. The research result show that there is a positive influence of the POE2WE learning model on students’ mathematical connection abilities.Keywords: the POE2WE learning model, mathematical connection abilities, Effect of learning